Health Services Trade and the COVID-19 Pandemic - Gillson, Ian; Muramatsu, Karen (World Bank, Washington, DC, 2020)
The COVID-19 (Coronavirus) pandemic has overwhelmed the capacity of some domestic healthcare systems, highlighting the need to allow scarce healthcare resources to move, including across borders, to where outbreaks emerge and are worse. Digital technologies, data, and cross-border e-health services like telemedicine have become important support mechanisms in the response to the pandemic. Allowing temporary movement of health professionals can also help alleviate capacity constraints on domestic health systems. In the short-term, countries can adopt measures to help alleviate national shortages of medical providers and facilitate the use of telemedicine in response to the COVID 19 pandemic. These include: (i) removing or lowering restrictions on the movement of healthcare professionals across borders, even if temporarily; and (ii) reducing barriers to telemedicine, including allowing the use of insurance in foreign clinics. Medium-term measures should focus on strengthening the global health system and building resilience to future crises. These include: (i) allowing foreign entry of health-related suppliers in order to bring additional resources, new technologies, and new management techniques; (ii) increasing cross-border coordination and collaboration between major research centers for disease prevention and control; and (iii) improving digital connectivity in order to provide better support for healthcare systems.